2008
DOI: 10.1149/1.2961823
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Emission Using Thin Li-Halide Cathodic Interlayers for Improved Injection into Poly(p-phenylene vinylene) Derivative PLEDs

Abstract: In this study, the effects of thin Li-halide cathodic interlayers on electron injection were examined for electroluminescent layers of polymer light-emitting diodes ͑PLEDs͒. An order of magnitude increase in current density is observed as Li-halide salts are varied down the group VII column of the periodic table. When considering luminance, devices with a LiCl interlayer were 2.3ϫ greater than those with LiF, whereas devices with LiBr were 2.8ϫ greater, while concurrently lowering the turn-on voltage. This res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…3 After that, many materials that could help to inject electrons into organic materials have been reported successively, and these compounds are mainly alkali metal salts. According to the anion of these salts, they can be classified alkali metal halide (such as NaF, 4 KF, 5 RbF, 6 CsF, 7 LiCl, 8 NaCl, 9,10 KCl, 11 RbCl, 12 CsCl 13 ), alkali metal carbonate (such as Li 2 CO 3 , 14 Na 2 CO 3 , 15 Rb 2 CO 3 , 16 Cs 2 CO 3 , [17][18][19][20] ), alkali metal nitrides (such as Li 3 N, 22 ), alkali metal (Li + , Na + , K + , Rb + , Cs + ) acetates, [24][25][26] organic alkali metal complexes (such as Liq (8-hydroxyquinolinato lithium), 27,28 Naq (8-hydroxyquinolinolato sodium), 29 Csq (cesium quinoline-8-oxide), 30 and so on. It is reported that alkali metal halide complexes can react with hot Al atoms impinging on them during the vapor deposition.…”
Section: Introductionmentioning
confidence: 99%
“…3 After that, many materials that could help to inject electrons into organic materials have been reported successively, and these compounds are mainly alkali metal salts. According to the anion of these salts, they can be classified alkali metal halide (such as NaF, 4 KF, 5 RbF, 6 CsF, 7 LiCl, 8 NaCl, 9,10 KCl, 11 RbCl, 12 CsCl 13 ), alkali metal carbonate (such as Li 2 CO 3 , 14 Na 2 CO 3 , 15 Rb 2 CO 3 , 16 Cs 2 CO 3 , [17][18][19][20] ), alkali metal nitrides (such as Li 3 N, 22 ), alkali metal (Li + , Na + , K + , Rb + , Cs + ) acetates, [24][25][26] organic alkali metal complexes (such as Liq (8-hydroxyquinolinato lithium), 27,28 Naq (8-hydroxyquinolinolato sodium), 29 Csq (cesium quinoline-8-oxide), 30 and so on. It is reported that alkali metal halide complexes can react with hot Al atoms impinging on them during the vapor deposition.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, one of the strategies used is to put a sub-monolayer of a thin alkali metal halide (i.e. LiF, LiBr, LiCl) [2][3][4] between the organic layer and the metallic cathode, and to use poly(ethylenedioxy) thiophene (PEDOT) doped with poly(styrene sulphonic acid) (PSS) 2,3 between the active polymer layer and the anode (usually indium tin oxide), that also works as a hole-transport layer. Although there is some controversy about the mechanism by which OLED efficiency is improved using these strategies 5 , several authors suggested that, for instance, LiF dissociate at the interface between the metallic cathode and poly(p-phenylene vinylene) (PPV), and lithium ions will diffuse through the polymer layer creating an hybrid ion doped region that enhances electron injection, whereas other authors suggest that the thin layer of polar metal halides between the metallic cathode creates a interfacial dipole, leading to strong band bending and thus to enhanced electron injection.…”
Section: Introductionmentioning
confidence: 99%